1988
DOI: 10.1111/j.1365-3083.1988.tb02334.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐Associated Changes in Murine Intestinal Immunoglobulin A and M Secretions

Abstract: The aging effect on the quantity of intestinal IgA and IgM class-specific immunoglobulins secreted and the quality of intraluminal intestinal IgA was studied in 5- to 6-month-old and 24- to 28-month-old male BALB/c mice. The level of IgA increased in the intestinal juice from the aged mice, while the IgM level remained unchanged. These alterations were similar to those found in serum, but the effect of age on serum IgA was profound, almost a threefold increase, in contrast to an increase of just under 35% in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…3c). This is not completely unexpected, as previous analyses have shown a similar difference in IgA levels between young and older mice in gut tissue [35, 36]. Interestingly, even though the frequency of local mucosal B cells in gut tissue is reduced in elderly mice, the synthesis and secretion of immunoglobulins was shown to be higher in older mice compared to young mice [35].…”
Section: Resultssupporting
confidence: 58%
“…3c). This is not completely unexpected, as previous analyses have shown a similar difference in IgA levels between young and older mice in gut tissue [35, 36]. Interestingly, even though the frequency of local mucosal B cells in gut tissue is reduced in elderly mice, the synthesis and secretion of immunoglobulins was shown to be higher in older mice compared to young mice [35].…”
Section: Resultssupporting
confidence: 58%
“…Some studies have reported increases or no change in the serum IgA levels in old animals and humans [26-29]. A few studies also reported the absence of age-related differences in the amounts of nonspecific immunoglobulins secreted into the intestinal lumen in vivo or into the medium by cultured duodenal biopsies [28-31], while other studies observed that the production of antigen-specific IgA is diminished with aging [14,32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…There is a depression in early signal transduction as well as a reduction in calcium fluxes (45)(46)(47)(48) in activated B and T lymphocytes in old animals. The levels of dimeric IgA produced in gut lamina propria as well as the number of CD4 + T cells in Peyers patches are significantly reduced in old animals (49,50).…”
Section: Immunoglobulin Isotypes Aging and Oral Tolerancementioning
confidence: 95%